NEGATIVE POLITENESS STRATEGIES USED BY MAIN CHARACTER IN “THE IMITATION GAME” - Julius; Ambalegin Ambalegin (IdeBahasa, 2021)
This research aims to find out types of negative politeness strategies expressed by the main character in the movie titled The Imitation Game. This research is categorised as descriptive qualitative research. The data of the research were taken from utterances identified as negative politeness strategies by the main character “Alan Turing” and analysed with theory proposed by (Brown & Levinson, 1988). Data were collected using the observation and non-participatory method. Additionally, to analyse the data, pragmatic identity method were used. The result discovered in this research are; 5 be conveniently indirect, 16 question and hedge, 1 be pessimistic, 6 give deference, 4 impersonalise interlocutors, and 4 state the FTA as the general rule, totalling to 36 indication of negative politeness strategies. Question and hedge became the most frequently used strategy the main character tends to assume unwillingness to comply to the other characters in The Imitation Game movie.